The diagnostic and prognostic value of IgG and IgA anti-citrullinated protein antibodies in patients with early rheumatoid arthritis - Sieghart, Daniela; Konrad, Christian; Swiniarski, Sascha; Haslacher, Helmuth; Aletaha, Daniel; Steiner, Günter (Frontiers in Immunology, 2023)
Objectives. Anti-citrullinated peptide antibodies (ACPA) are specific markers for rheumatoid arthritis (RA) and typically measured by assays employing a cyclic citrullinated peptide (CCP) as antigen. This study was aimed at investigating the diagnostic performance of anti-CCP2 and anti-CCP3 IgG and IgA assays in patients with early rheumatoid arthritis (RA) with a particular focus on the potential prognostic value of IgA ACPA. Methods. The anti-CCP3.1 assay (Inova Diagnostics) measuring IgG and IgA antibodies simultaneously was compared to anti-CCP2 IgG and IgA assays (Thermo Fisher Scientific) employing sera of 184 early RA patients, 360 disease controls and 98 healthy subjects. Results. Anti-CCP2 IgG and IgA assays showed high specificity versus disease controls (98.9%; 99.4%). Sensitivity was 52.2% (IgG) and 30.428.8% (IgA), resulting in positive likelihood ratios (LR+) of 47.5 (IgG) and 50.748.0 (IgA). The anti-CCP3.1 assay proved slightly more sensitive than the anti-CCP2 IgG assay (56%) but specificity was markedly lower (90.8% versus disease controls). However, when using a threefold higher cut-off specificity of the anti-CCP3.1 assay increased (97.5%) while sensitivity (52.7%) became comparable to the anti-CCP2 IgG assay resulting in a LR+ of 21.5. Anti-CCP2 IgA antibodies did not increase the diagnostic sensitivity of ACPA testing, but IgA positive patients showed diminished responses to treatment with anti-TNF biologicals compared to patients who had only IgG antibodies. Conclusion. Specificity of ACPA assays should be adjusted to reduce the risk of misclassification and a false positive diagnosis. Determination of ACPA IgA might provide important prognostic information concerning therapeutic responses.